The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2022
DOI: 10.1108/imds-09-2021-0600
|View full text |Cite
|
Sign up to set email alerts
|

The impact of gamification on teaching and learning Physical Internet: a quasi-experimental study

Abstract: PurposeToday's logistics industry is facing severe challenges since global transportation demand increases substantially. Carriers are urged to reduce empty loads and CO2 emissions through collaboration. Therefore, the concept of Physical Internet (PI) came into being. However, PI is still in its infancy. It is difficult to understand its sophisticated coordination mechanism, which makes learning of the concept more complicated.Design/methodology/approachGamification is an effective approach to help students i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 44 publications
0
2
0
Order By: Relevance
“…Por su parte, Sannathimmappa et al (2022) encontraron que los estudiantes disfrutaron de los juegos, los encontraron divertidos e interesantes, y les ayudaron a comprender los temas y mejorar su metodología de estudio. Wang et al (2022) observaron cambios positivos en el comportamiento y la psicología de los participantes chinos, además de mejoras en el pensamiento crítico y las habilidades de aprendizaje. Por su parte, Wannapiroon y Pimdee (2022) encontraron que el diseño gamificado fortalece la creatividad, la crítica y el pensamiento innovador en los estudiantes, y Rui et al (2020) demostraron que la gamificación fomenta la ideación y el desarrollo de habilidades críticas.…”
Section: Discussionunclassified
“…Por su parte, Sannathimmappa et al (2022) encontraron que los estudiantes disfrutaron de los juegos, los encontraron divertidos e interesantes, y les ayudaron a comprender los temas y mejorar su metodología de estudio. Wang et al (2022) observaron cambios positivos en el comportamiento y la psicología de los participantes chinos, además de mejoras en el pensamiento crítico y las habilidades de aprendizaje. Por su parte, Wannapiroon y Pimdee (2022) encontraron que el diseño gamificado fortalece la creatividad, la crítica y el pensamiento innovador en los estudiantes, y Rui et al (2020) demostraron que la gamificación fomenta la ideación y el desarrollo de habilidades críticas.…”
Section: Discussionunclassified
“…The researchers used simulation software to construct practical project assignments, which significantly increased students' involvement in teaching activities. Literature [21] designed and implemented a transportation teaching game in the context of information technology teaching, oriented to the learning difficulties of the Internet of Things, and constructed a gamified experimental teaching process. A series of statistical analyses demonstrated that the teaching method enhances students' understanding of knowledge.…”
Section: Status Of Researchmentioning
confidence: 99%
“…The essence of educational gamification is to motivate students to actively engage, enabling them to achieve the desired learning objectives while also experiencing the enjoyment of playing games [11]. Therefore, effective evaluation of students' learning participation not only helps teachers understand their actual learning situations but also provides educators with more targeted teaching strategies [12][13][14][15][16]. In addition, conducting a thorough analysis of interactive evolution in the process of educational gamification helps to uncover the dynamic relationships between students, educational content, and teachers.…”
Section: Introductionmentioning
confidence: 99%